2022
DOI: 10.18176/jiaci.0542
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to Gibberellin-Regulated Protein (Peamaclein) Among Italian Cypress Pollen–Sensitized Patients

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, types etting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…21 The exact role of cypress pollen in relation to PFAS is yet unknown and subject of current research. [22][23][24][25] Pollen food allergy syndrome cross-reactions are caused by plant-food allergens that share sequence, structure, and function similarities with pollen allergens. Due to their widespread nature, these are known as panallergens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The exact role of cypress pollen in relation to PFAS is yet unknown and subject of current research. [22][23][24][25] Pollen food allergy syndrome cross-reactions are caused by plant-food allergens that share sequence, structure, and function similarities with pollen allergens. Due to their widespread nature, these are known as panallergens.…”
Section: Introductionmentioning
confidence: 99%
“…One of these is cypress pollen, a primary cause of SAR in the Mediterranean 21 . The exact role of cypress pollen in relation to PFAS is yet unknown and subject of current research 22‐25 …”
Section: Introductionmentioning
confidence: 99%
“…The researchers from France described the peach GRP as a major allergen in the patients allergic to peach from southern France, where the exposure to cypress pollen is high, with a prevalence of Pru p 7 sensitization exceeding 60% (9,28). In contrast, a recent study reported that the allergy and sensitization to foods secondary to cypress pollen allergy appeared as rare phenomenon in the Italian population and that most of such patients react to peach, rather than other Rosaceae fruits (29). Therefore, discrepant results concerning the allergenic properties of GRP can sometimes be found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Based on its geographic distribution, cypress pollen is another putative candidate as a primary sensitizer to lipid transfer protein (328). Nowadays we know that cypress pollen is the primary sensitizer to gibberellin-regulated protein, which is associated with systemic reactions to different fruits, particularly the peach (33,34). To our knowledge, there are no data regarding an association with food LTP hypersensitivity and besides, no LTPs have been identified in cypress pollen so far…”
Section: Cypress (Cupressus Arizonica)mentioning
confidence: 99%